Nanometre-Scale Biosensors for Applications in Medicine/Environment/Food/Biomedical Research - LO, Pik Kwan Peggy (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint serves as an introduction to the groundbreaking research work that explores the remarkable advancements in biosensor technology and its profound impact on the fields of biomedicine and environmental research. It aims to elucidate the subject's scope, provide future research directions, and highlight potential applications. This reprint is dedicated to the scientific community, researchers, and professionals seeking to expand their knowledge of biosensing. We express our gratitude to all those who have supported and contributed to this scientific endeavor.